Using Kahoot! learning game media to improve students' learning results in 5th grade on Islamic Education and Character Lesson - Rochmat, Cecep Sobar; Huwaida, Jaziela; Hayati, Nur; Qolbi, Safira Naurin; Novera, Samia (LPPM Universitas Ibn Khaldun, Bogor, 2025)
This study aims to investigate the impact of using Kahoot! learning game media on the academic performance of fifth-grade students in Islamic Education and Character lessons. The research employed the McTaggart Classroom Action Research (CAR) method, consisting of two cycles that included planning, implementation, observation, and reflection stages. The results indicate a significant improvement in students' academic achievement, with the mastery level increasing from 94.74% in the first cycle to 100% in the second cycle. The use of Kahoot! as a game-based learning medium proved effective in enhancing student engagement, participation, conceptual understanding, and material retention. This study highlights the importance of innovative and technology-based teaching strategies to improve learning effectiveness. The implementation of interactive media such as Kahoot! can serve as a solution for educators to create a more dynamic and engaging learning experience for students. AbstrakPenelitian ini bertujuan untuk menyelidiki dampak penggunaan media permainan pembelajaran Kahoot! terhadap hasil belajar siswa kelas lima dalam mata pelajaran Pendidikan Agama Islam dan Budi Pekerti. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) McTaggart dengan dua siklus yang mencakup tahap perencanaan, pelaksanaan, observasi, dan refleksi. Hasil penelitian menunjukkan peningkatan signifikan dalam capaian akademik siswa, dengan rata-rata ketuntasan belajar meningkat dari 94,74% pada siklus pertama menjadi 100% pada siklus kedua. Penggunaan Kahoot! sebagai media pembelajaran berbasis game terbukti mampu meningkatkan keterlibatan dan partisipasi siswa dalam kelas, memperbaiki pemahaman konsep, serta meningkatkan retensi materi. Studi ini menekankan pentingnya strategi pembelajaran yang inovatif dan berbasis teknologi untuk meningkatkan efektivitas pembelajaran. Implementasi media interaktif seperti Kahoot! dapat menjadi solusi bagi guru dalam menciptakan pengalaman belajar yang lebih dinamis dan menarik bagi siswa.